An unorthodox presentation of multiple myeloma in the form of acute ischemic stroke, dyspnoea, thromboses in multiple arteries and abdominal pain: A case report - Tambolkar, Ajit; Tambolkar, Isha; Navandar, Raghav (Indian Journal of Case Reports, 2022)
A patient with multiple myeloma usually presents with pathologic fractures, renal failure, anemia, and recurrent bacterial infections. Instead, this patient presented with acute ischemic stroke, dyspnea, and abdominal pain. The following case could be of immense clinical significance due to the unorthodox presenting features of the patient. A 55-year-old Indian male, a known hypertensive with a history of COVID-19, presented with features of acute ischemic stroke, breathlessness, and moderate abdominal pain. After treating the stroke, USG abdomen and pelvis were done which showed aortic, splenic, and right renal arterial thrombosis. Following suspicious laboratory results, a bone marrow biopsy was performed which revealed 12–15% plasmacytosis. Serum electrophoresis showed a band of M-protein suggestive of multiple myeloma. Multiple myeloma is rare and the aforementioned symptoms are even rarer which could pose a diagnostic challenge to clinicians. Clinicians should consider the possibility of multiple myeloma in similar cases in the future.